MINDS OF THE FUTURE: ENTREPRENEURIAL, INNOVATIVE AND TECHNOLOGICAL EDUCATION - Cristina Sayuri Côrtes Ouchi Dusi; Thiago Gomes de Almeida; Giovani Peterson Alves Mendes; Raquel Rodrigues da Silva Melo (ARACÊ, 2025)
This article presents partial results of a Brazilian entrepreneurial education project named Minds of the Future. This project is aimed at low-income high school students from public schools in the city of Juiz de Fora, Minas Gerais State, Brazil. Developed through a collaboration between Federal University of Juiz de Fora and Minas Gerais Education Department, the project aims to contribute for a transformative education, focused on training young people to cope with new life realities, social relationships, and work through the stimulation of critical, creative, technological and entrepreneurial thinking. This project is justified both by the need for young people’s engagement in the rapid advances in systems and data automation and by the educational reality of the country, which has a high dropout rate during the transition between elementary and high school.The proposed approach to knowledge transfer and sharing is STEAM. In the first stage, Lego® Education robotics materials were used, which combine Lego® construction elements and intuitive programming language in a 12-hour module of lessons and playful activities offered to 135 students distributed in eight classes during 2024. This and other modules involving 3D modeling, soft skills, financial education and sustainable development will be offered in the second semester of 2024. The project includes professors from different areas and 14 scholarship holders from different undergraduate courses at the Federal University of Juiz de Fora - physics, engineering, computer science, business administration, accounting, law, nutrition and pedagogy - who acted as facilitators during the classes and activities developed. To evaluate the results of this initial experience with the application of the Lego programming and robotics module, a qualitative and quantitative research was conducted. Questionnaires with objective questions were administered to the students via Google Forms at the beginning of the first class and at the end of the last class of the module. Additionally, questionnaires with both objective and open-ended questions were given to the project scholarship holders. Minds of the Future project demonstrated significant positive impacts both among the students and the participating scholarship holders perceptions and skills. The results indicate improvements in various dimensions, from the relationship with teachers to the development of technical skills and increased interest in technology and innovation.